YOUNG WOMEN DIGITAL COMPETENCE IN USING THE INTERNET IN SURABAYA - Yuli Candrasari; Salshabilla Permata; Afifah Rachmania; Dyva Claretta (Profetik: Jurnal Komunikasi, 2020)
The growth in the number of netizens is now the impact of increasingly easy internet penetration and high penetration of social media that is easily accessed via smartphone gadgets. Research conducted by Candrasari (2016) states that female internet users cannot be separated from their social media. Within a day of 2-3 hours, his time is spent accessing digital media. Therefore digital competencies are needed for girls to avoid the negative effects of the internet. The purpose of this study is to get a picture of the competence of adolescent girls. Digital competence is a form of using technology safely and critically to facilitate work, get entertainment and to communicate (E. Encabo & Murcia, J: 2011: 166). This research was conducted on adolescent girls in Surabaya with qualitative research methods. Data obtained through in-depth interviews, participant observation, and literature studies. The results of the study indicate that the digital competence of adolescent girls is still not good, especially in the categories of skills using the internet, information management and responsibility for using internet which is still low. Only in the category of communication and sharing digital competence of young women is good